VISUALISASI POTENSI LOKASI WISATA HERITAGE DI KOTA SEMARANG BERBASIS ANDROID (Information Technology and Telematics, 2015)
Abstract- Technological developments, particularly in information and communication technology has grown very rapidly and has been attached to people's lives. This makes humans like never separated by distance, space, and time. With the development of increasingly advanced technology, people can create a wide range of equipment that is used as an aid in carrying out various activities to support productivity. The method used to create or develop new software is a prototype model. This method is a method of system development where the results of analyzes per section directly implemented into a model without having to wait the entire system is completed. Visualization potential heritage tourist sites in the city of Semarang can be used to view information heritage tourism in the city of Semarang that heritage tourism in the city of Semarang increasingly recognized by the public. Visualization potential heritage tourist sites in the city of Semarang can be used to display the profile information is displayed in text form, the gallery is displayed in the form of pictures, videos are displayed in the form of video and location are displayed in the form google maps marker of heritage tourism in the city of Semarang Keywords – Location Tourism, Heritage, Android